2013
DOI: 10.1186/1754-6834-6-7
|View full text |Cite
|
Sign up to set email alerts
|

Cofactor engineering through heterologous expression of an NADH oxidase and its impact on metabolic flux redistribution in Klebsiella pneumoniae

Abstract: BackgroundAcetoin is an important bio-based platform chemical. However, it is usually existed as a minor byproduct of 2,3-butanediol fermentation in bacteria.ResultsThe present study reports introducing an exogenous NAD+ regeneration sysytem into a 2,3-butanediol producing strain Klebsiella pneumoniae to increse the accumulation of acetoin. Batch fermentation suggested that heterologous expression of the NADH oxidase in K. pneumoniae resulted in large decreases in the intracellular NADH concentration (1.4 fold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 41 publications
1
38
0
Order By: Relevance
“…Considering the role of C. glutamicum cells in metabolite overproduction and the importance of cofactor regeneration such as NAD + /NADH cycling in metabolic engineering (Hou et al 2014;Ji et al 2013;Rocha-Martin et al 2011;Zhang et al 2014), the noxA gene may be of importance in the field of biotechnology. Toward fully elucidating the function of noxA in C. glutamicum physiology, additional investigations are underway.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the role of C. glutamicum cells in metabolite overproduction and the importance of cofactor regeneration such as NAD + /NADH cycling in metabolic engineering (Hou et al 2014;Ji et al 2013;Rocha-Martin et al 2011;Zhang et al 2014), the noxA gene may be of importance in the field of biotechnology. Toward fully elucidating the function of noxA in C. glutamicum physiology, additional investigations are underway.…”
Section: Discussionmentioning
confidence: 99%
“…Except for KG-rs, all the recombinant mutants exhibited slow growth rate and high by-product yield; such factors may be the reasons why the 2,3-BD yields did not significantly increase. Previous studies have shown that protein overproduction does not always increase the corresponding product yields; on the contrary, this overproduction may be detrimental to cell growth [18,31]. The same phenomenon was observed in other strains, such as Saccharomyces cerevisiae [25], in which only the constitutive expression of protein can dramatically increase the cell growth and improve the fermentation efficiency.…”
Section: Discussionmentioning
confidence: 58%
“…Metabolic engineering is widely used to improve the properties of microbial strains, such as manipulating the key enzyme levels through the amplification, disruption, or addition of metabolic pathways [18,[24][25][26]. This study demonstrates that the overexpression of the key enzymes for 2,3-BD biosynthesis caused by a strong promoter increases 2,3-BD production in K. pneumoniae.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…An interesting benefit of this ldhA deletion was an increase in microbial cell growth [22]. Generally, a metabolically engineered microorganism has reduced cell growth compared with the wild type strain [32,33]. The increased microbial cell growth of the mutant could be largely attributed to the reduced production of lactic acid, which lowers the acidification rate of the media [34].…”
Section: Metabolic Engineering Of Aerogenes Atcc 29007 To Ferment Biomentioning
confidence: 98%